Biotechnologies for Plant Mutation Breeding: Protocols - Jankowicz-Cieslak, Joanna; Tai, Thomas H.; Kumlehn, Jochen; Till, Bradley J.; Jankowicz-Cieslak, Joanna; Tai, Thomas H.; Kumlehn, Jochen; Till, Bradley J. (Cham Springer Nature, 2017)
Plant Breeding/Biotechnology; Agriculture; Genetic Engineering; Plant Genetics & Genomics
English
Keywords: Manufacturing industries; Biochemical engineering; Plant Breeding/Biotechnology; Agriculture; Genetic Engineering; Plant Genetics & Genomics